2014
DOI: 10.1155/2014/731296
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Erythropoiesis-Stimulating Agents Is Associated with Arterial Microcalcification in Early Hemodialysis Patients

Abstract: The aim of this study was to evaluate the relationship between arterial microcalcification (AMiC) and erythropoiesis-stimulating agents (ESA) hyporesponsiveness in hemodialysis patients. The presence of AMiC was confirmed by pathologic examination of von Kossa-stained arterial specimens acquired during vascular access surgery. We assessed the ESA hyporesponsiveness index (EHRI), defined as the weekly ESA dose per kilogram body weight divided by the hemoglobin level. AMiC was detected in 33 (40.2%) of 82 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Therefore, retained β2-microglobulin seems to further contribute to the vascular calcification process in the uremic milieu. In addition, oxidative stress and inflammation are also considered to play a key role [ 5 ]. Interestingly, Won et al showed that ESA resistance was associated with vascular calcification, which could be explained based on oxidative stress and inflammation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, retained β2-microglobulin seems to further contribute to the vascular calcification process in the uremic milieu. In addition, oxidative stress and inflammation are also considered to play a key role [ 5 ]. Interestingly, Won et al showed that ESA resistance was associated with vascular calcification, which could be explained based on oxidative stress and inflammation [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress and inflammation are also considered to play a key role [ 5 ]. Interestingly, Won et al showed that ESA resistance was associated with vascular calcification, which could be explained based on oxidative stress and inflammation [ 5 ]. Meanwhile, Stompor et al described that higher residual renal function in dialysis patients was responsible for better clearance of proinflammatory cytokines [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a paucity of published anaemia management studies that incorporated various RI measures, and most focused specifically on the ERI RI. The RI was utilized to explore such relationships as the effect of high‐flux dialysis (Schneider et al 2012), dialysate purity (Molina et al 2007), pentoxifylline (Johnson et al 2014), arterial microcalcification (Won et al 2014), cardiovascular events (Chung et al 2012), left ventricular function (Chung et al 2012), choice of medication (ERI vs DRI) (Portolés et al 2008), route (subcutaneous or intravenous) (Bommer et al 2008) or frequency of administration (Molina et al 2008) on ESA dosing and resistance. The weakness of a few reports, which included patients on DRI, was that they mathematically converted its dosing to that for ERI using a fixed 1:200 ratio (Bommer et al 2008; Portolés et al 2008; Johnson et al 2014; Won et al 2014).…”
Section: Discussionmentioning
confidence: 99%